PERSONAL ASPIRATIONS: EMPIRICAL RESEARCH - Hulias, Inesa (PSYCHOLOGICAL JOURNAL, 2019)
The article is devoted to an important psychological phenomenon – personal aspirations. The concept under consideration is disclosed at the intersection of studies of the motivational structure of the person, purpose-setting, features of the structuring of the future and the subject’s human activity.It is stated that the desire is formed on the basis of the physical, biological, social and psychological needs of the person, based on the requirements of society and embodied through the choice of specific goals and objectives. It is noted that personal aspirations reflect the typical or characteristic tasks that a person wants to perform in his everyday life, and are important sources of his content.In order to study the personal aspirations of a recognized psychological instrument – the method of «Evaluation package of personal aspirations» R. Emmons. The study was attended by 90 respondents aged 20-25 in the specialty «Psychology». The survey was conducted on the basis of the faculty of pedagogy, psychology and social work of Chernivtsi National University named after Yuriy Fedkovich.It is concluded that almost one third (27.8%) of respondents are aimed at personal growth and health preservation; Second place was the pursuit of achievement (16.3%); the third – self-presentation (13.7%); in the fourth position – the desire for intimacy (12.7%); the fifth – with communication (9.5%). Creative productivity and self-sufficiency / independence have a small percentage of expression (8.37% and 6.3% respectively). Only 3.41% of respondents have intentions for spiritual transcendence. The desire for power and misadaptation (by 0.96%, respectively) in the sample are irrelevant.In the respondents, the topic of success and positive emotions prevails, in other words, they successfully advance in the realization of their aspirations (5.5), more or less progress (3.87) and, in the end, also hope for a positive result and the likelihood of success (6, 88), and, therefore – rejoice (3,38). Respondents consider their own aspirations to be, to some extent, important (3.6) and, in part, socially desirable (2.63). In goal-setting, students are completely independent, however, and somewhat take into account the opinion of others (2.33).Positive correlation shows that important and complicated goals require the efforts (and not only volitional ones), which are related to the implementation of actions. Successful implementation of the activity is possible only with the long motivation, persistence in the implementation of the program and plans, rational spending time and energy; the successful realization of certain ideas that are liked by others and useful for them, are socially desirable (otherwise, success often causes envy and aggression in the surrounding environment); life circumstances determine the design of personality representations in achieving the goal; internal motivation (as well as autonomy), clarity of implementation of steps towards the goal, respondents received support from relatives in the implementation of their aspirations.Negative correlations demonstrate that the experience of negative emotions, in particular sadness, does not contribute to the success of the implementation of certain projects and plans; life circumstances (the situation in general, the health of relatives and relatives, the financial situation) are constrained in the implementation of certain plans; programs and projects that are important to others do not have the support of loved ones; successful realization of their goals and intentions is possible only in the presence of their own desires and beliefs.